Correlation in formation of 8Be nuclei and α-particles in fragmentation of relativistic nuclei - A.A. Zaitsev (Physics Letters B, 2021)
In the events of peripheral dissociation of relativistic nuclei in the nuclear track emulsion, it is possible to study the emerging ensembles of He and H nuclei, including those from decays of unstable 8Be and 9B nuclei, as well as the Hoyle state. These extremely short-lived states are identified by invariant masses calculated from the angles in 2α-pairs, 2αp- and 3α-triplets in the approximation of conservation of momentum per nucleon of the primary nucleus. In the same approach, it is possible to search for more complex states. This paper explores the correlation between the formation of 8Be nuclei and the multiplicity of accompanying α-particles in the dissociation of relativistic 16O, 22Ne, 28Si, and 197Au nuclei. On the above basis, estimates of this correlation are presented for the unstable 9B nucleus and the Hoyle state. The enhancement in the 8Be contribution to dissociation with the α-particle multiplicity has been found. Decays of 9B nuclei and Hoyle states follow the same trend.